2014
DOI: 10.1002/eji.201343645
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in heparanase exhibit impaired dendritic cell migration and reduced airway inflammation

Abstract: Heparanase is a β-D-endoglucuronidase that cleaves heparan sulphate, a key component of the ECM and basement membrane. The remodelling of the ECM by heparanase has been proposed to regulate both normal physiological and pathological processes, including wound healing, inflammation, tumour angiogenesis and cell migration. Heparanase is also known to exhibit non-enzymatic functions by regulating cell adhesion, cell signalling and differentiation. In this study, constitutive heparanase-deficient (Hpse −/− ) mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 55 publications
2
63
0
Order By: Relevance
“…Notably, heparanase gene silencing resulted in decreased delayed-type hypersensitivity (DTH) reaction (Edovitsky et al, 2006), and heparanase knockout mice showed reduced airway and acute lung injury responses in models of allergy and sepsis (Poon et al, 2014; Schmidt et al, 2012). Furthermore, transgenic mice overexpressing heparanase are endowed with increased DTH (Edovitsky et al, 2006), colon (colitis) (Lerner et al, 2011), pancreas (unpublished data) and skin (psoriasis-like) (Lerner et al, 2014) inflammation, collectively implying that heparanase is an important player in the inflammatory reaction (Goldberg et al, 2013; Li and Vlodavsky, 2009; Zhang et al, 2014).…”
Section: Heparanase In Acute and Chronic Inflammationmentioning
confidence: 99%
“…Notably, heparanase gene silencing resulted in decreased delayed-type hypersensitivity (DTH) reaction (Edovitsky et al, 2006), and heparanase knockout mice showed reduced airway and acute lung injury responses in models of allergy and sepsis (Poon et al, 2014; Schmidt et al, 2012). Furthermore, transgenic mice overexpressing heparanase are endowed with increased DTH (Edovitsky et al, 2006), colon (colitis) (Lerner et al, 2011), pancreas (unpublished data) and skin (psoriasis-like) (Lerner et al, 2014) inflammation, collectively implying that heparanase is an important player in the inflammatory reaction (Goldberg et al, 2013; Li and Vlodavsky, 2009; Zhang et al, 2014).…”
Section: Heparanase In Acute and Chronic Inflammationmentioning
confidence: 99%
“…DNA was purified from FACS-sorted mouse NK cells using QuickExtract DNA Extraction Solution (Epicentre). The primer sets and conditions for expression of the mouse Hpse gene have been published previously (6). For genotyping of the NKp46-iCre allele, the following primers were used in 1 reaction (giving rise to a product of approximately 400 bp for the WT …”
Section: Mouse Nk Cell Activationmentioning
confidence: 99%
“…In mammals, the only enzyme known to degrade HSPGs is the endo-β-D-glucuronidase heparanase. There is only 1 enzymatically active form of heparanase in mammals that is expressed at very low levels in normal tissues, and heparanase deficiency in mice causes no obvious pathophysiologies (5,6). Heparanase is secreted as an enzymatically inactive pro-heparanase and requires reuptake into the cell and processing by cathepsin-L in lysosomes (7) or α granules (8) in order to give rise to the enzymatically active heparanase protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this notion, heparanase up-regulation was observed in different inflammatory conditions [25-28] and is thought to promote inflammation. Indeed, heparanase gene silencing resulted in decreased delayed-type hypersensitivity reaction [25], and heparanase knockout mice showed reduced airway and acute lung injury responses in models of allergy and sepsis [29,30]. Furthermore, transgenic mice over expressing heparanase are endowed with increased colon (colitis) and skin (psoriasis-like) inflammation [26,31], collectively implying that heparanase is an important player in the inflammatory reaction [32-35].…”
Section: Discussionmentioning
confidence: 99%